Etos Kerja Guru MI Bersertifikat Profesional - Choirun Nisaa'; Ardi Rispurwanto (Dawuh Guru: Jurnal Pendidikan MI/SD, 2021)
Law Number 14 of 2005 concerning Teachers and Lecturers states that every teacher is required to have four basic competencies, namely pedagogical competence, personality competence, professional competence, and social competence. The research objective was to determine the relationship between teacher work ethics and professional certificates. The method of this research is a qualitative descriptive approach related to work ethic and then the correlation is sought with professional certificates through quantitative methods. The subjects of this study were 16 teachers of Madrasah Ibtidaiyah (MI) in Pundong District, Bantul Regency, Yogyakarta. The results showed that teachers who were certified professional educators had good competence and high work ethic. Based on the results of the product moment correlation analysis, it was obtained a correlation coefficient (rxy) of 0.087 with p = 0.750, which means that there is a relationship between teacher work ethics and professional educator certificates, but the correlation is very weak or very low.